Factors associated with dental caries experience and oral health status among New South Wales adolescents - John Skinner; George Johnson; Anthony Blinkhorn; Roy Byun (Elsevier, 2014)
Abstract Objective: To investigate the potential social and behavioural risk factors influencing the oral health of teenagers aged 14 and 15 years living in New South Wales Australia. Methods: Quantitative and qualitative methodologies were used in this research project. Data were obtained from both the clinical and questionnaire components of the NSW Teen Dental Survey 2010 and were analysed in SAS 9.2. The analyses allowed for various demographic and behavioural risk factors to be assessed using caries experience, severe caries and DMFT (decayed, missing or filled teeth) counts as the key outcome variables. Results: Of the 1,256 14- and 15‐year‐olds who had a dental examination, 1,199 (95.5%) provided questionnaire data. The clinical examinations found that 44.4% of teenagers overall had caries experience in at least one tooth, while 10.6% of the sample had experienced severe caries. Severe dental caries was found to be significantly related to a variety of factors, including family income, fluoridation status, tooth brushing behaviour and sugary drink consumption. Conclusions: The oral health of 14- and 15‐year‐olds in NSW is influenced by social and dietary factors as well as access to fluoridated water supplies. There was also a strong relationship between self‐rated oral health status with DMFT and with caries experience. Implications: The findings of this study will assist policy makers by highlighting the current caries risk factors that should be part of future health promotion programs.